A tradução intravisual e intralingual de A walk in the Park para Voices in the Park: um estudo sociossemiótico da reinstanciação - Cristina Lazzerini de Souza (2022)
This thesis presents a study which applied the concepts and the categories of Social Semiotics to Translation Studies in a multidisciplinary approach to investigate picture books. The aims were to interpret reinstantiation as translation and to relate the concepts of rewriting (LEFEVERE, 1992) and reinstantiation (MARTIN, 2006, 2008c). The books investigated were A Walk in the Park and Voices in the Park, by the author and illustrator Anthony Browne. The study used Painter, Martin and Unsworth (2013)’s model of reading visual narratives and Martin and Rose (2007)’s model of discourse semantics to investigate the ideational and interpersonal resources in the visual and verbal modalities of the bimodal text. It further employed the notions of coupling and commitment (MARTIN, 2006, 2008c, 2010) to analyse intermodality and intertextuality, and the complementarity of the hierarchies of realisation, instantiation and individuation (ibid) to analyse the semantic variations. It focused on the dimensions of social inequality in the stories and the positioning of the prospective reader. The methodology consisted of three stages dedicated respectively to the analysis of the generic structure of the texts, to the identification and classification of the semiotic resources which construe the meanings in the texts, and to the identification and analysis of the semantic variations in the reinstantiation of the source text. The interface between the Social Semiotics for multimodality and the cultural branch of Translation Studies was created through the concept of ideology and it allowed to establish that reinstantiation is the same as rewriting. The study operationalized a methodology for the investigation of reinstantiation in the visual modality, and its application made it possible to demonstrate that visual reinstantiation occurs mainly through the overlapping of ideational meaning potential between the images of the two stories. Finding that the visual narratives in Voices in the Park reconstrue the visual narrative in A Walk in the Park, with distinct images which present various degrees of meaning overlapping in relation to the source text, resulted in the proposal of three levels of visual reinstantiation. The study proposed the concept of reillustration, parallel to that of rewriting, for the type of reinstantiation which occurs between visual narratives. In reference to Jakobson (1959), the phenomenon of interpreting visual signs by means of other visual signs which occurs in reillustration was denominated intravisual translation. The results confirmed that A Walk in the Park privileges the use of ideational resources to construe semantic parallelism and to emphasize the dimension of social class, and that the addition of interpersonal resources in Voices in the Park functions to construe the individualities and the ideologies of the character-narrators. The results also showed that the semiotic resources used to construe the dimensions of inequality are mainly ideational in both texts and that the manipulation of the semiotic resources in Voices in the Park served to dealign the prospective reader with the values of the bourgeois middle class woman and to naturalise the discourse of the working class child, aligning the reader with the values of this character-narrator, and disclosing the political role of the translation.